Imidazoline receptor agonists: more than blood pressure reduction? - D. V. Nebieridze; S. V. Nedogoda (Кардиоваскулярная терапия и профилактика)
The review contains original data and international studies’ results demonstrating that selective I1 imidazoline receptor agonists, and, in particular, Albarel®, a new sympatholytic agent, provide not only adequate and longterm blood pressure control, but also other beneficial metabolic and vascular effects. Most important ones are insulin resistance reduction, improvement of endothelial function and elasticity in middle-sized and large vessels. In Russian guidelines on arterial hypertension diagnostics and treatment, this medication class is recommended in patients with metabolic disturbances. Nevertheless, in real-world clinical practice, the indications might be widened, including sympathetic hyperactivity in post-menopause women, patients with insulin resistance, chronic obstructive pulmonary disease, and bronchial asthma.